Pelatihan pembuatan sabun kertas kepada anggota PKK Kelurahan Sukamiskin dalam upaya mencegah penyebaran Covid-19 - Emma Emawati; Raden Siti Jundiah; Yuli Astuti; Cici Valiani; Mia Nisrina; Nur Intan Hayati Husnul Khotimah (Abdimas Siliwangi, 2023)
PKK for Sukamiskin Village is an organizational group of PKK mothers from 17 RWs in the Sukamiskin Village, Antapani District, Bandung City.In the Era of the Covid-19 Pandemic, every individual must always be aware of maintaining cleanliness, applying the habit of wearing masks and washing hands to prevent the spread of the virus that causes Covid-19. Washing hands with soap is an effective effort for all people to prevent the spread of the virus that causes Covid-19. Soap is amphiphilic, that is, the head has a hydrophilic (polar) and hydrophobic (nonpolar) group. Therefore, soap can bind dirt and fat molecules and dissolve them in water. Hand washing soap that is practical to carry anywhere is something that is needed by today's society. Paper soap is one of the innovative soap products. This paper soap will dissolve when exposed to water and rubbed on the hands will release foam. Paper soap is generally used as disposable hand soap because of its small and thin size, which makes it easy to carry anywhere and is suitable for use when doing activities outside the home. This is the reason for the importance of providing knowledge and skills to PKK mothers about the importance of washing hands and skills in making paper soap so that the application of hand washing habits can be cultivated.